Contributions of research as an axis of Science teaching courses: a survey on students' ideas about Organic Chemistry - Souza, Diana de Meneses (2013)
The aim of this study was to identify, in high school students of Barreiras/Bahia, the so-called alternative conceptions about organic chemistry topics. The object of analysis emerged from the research approach in the classroom. These concepts were investigated based on the stages of research in the classroom: questioning, argument construction and communication of results. This process showed that the organic chemistry conceptions of the surveyed high school students presented elements of vitalism and non-reactivity of organic compounds. Furthermore, they had the idea that any carbon-containing compound was an organic compound.